2020
DOI: 10.1002/1873-3468.13912
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial multi‐solute transporters

Abstract: Bacterial membrane proteins of the SbmA/BacA family are multi-solute transporters that mediate the uptake of structurally diverse hydrophilic molecules, including aminoglycoside antibiotics and antimicrobial peptides. Some family members are full-length ATP-binding cassette (ABC) transporters, whereas other members are truncated homologues that lack the nucleotidebinding domains and thus mediate ATP-independent transport. A recent cryo-EM structure of the ABC transporter Rv1819c from Mycobacterium tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Studies have shown that a mutant bacillus of rv1819c loses the ability to maintain chronic infection in murine models and increases resistance to bleomycin [82]. Besides the previous functions attributed to Rv1819c, it is also speculated to play a role in the transport of peptides and drugs [31].…”
Section: Hydrophilic Compoundsmentioning
confidence: 99%
“…Studies have shown that a mutant bacillus of rv1819c loses the ability to maintain chronic infection in murine models and increases resistance to bleomycin [82]. Besides the previous functions attributed to Rv1819c, it is also speculated to play a role in the transport of peptides and drugs [31].…”
Section: Hydrophilic Compoundsmentioning
confidence: 99%
“…Thus, we need atomic structures reflecting more than a single conformation and possibly many transition states [ 352 ], as well as extensive validation by biochemistry and genetics, to validate their biological relevance and define catalytic cycles. Furthermore, there is an unmet need for more interdisciplinary collaborations that also engage alternative structural approaches like NMR [ 353 , 354 , 355 , 356 ] as well as complementary biophysical methods [ 265 , 357 , 358 , 359 ] to expand our mechanistic views of ABC transporters in all living kingdoms.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In the case of OaBac5mini, the peptide appeared to kill E. coli using intracellular sites of action that were proposed to include protein and DNA synthesis 99,105 , which was supported by other studies 34,106 , although mechanisms used by the peptide to cross the inner membrane of the organism were not determined 99,105 . However, a close bovine homologue of OaBac5mini appeared to kill E. coli using nonmembranolytic mechanisms that involved internalization via SbmA [107][108][109] , an inner membrane transporter 110 , and the blocking of protein synthesis, facilitated by the homologue's extended, polyproline helical structure [107][108][109] . The use of Sbma and MdtM, which is also an inner membrane transporter 111 , facilitates the antibacterial action other proline-rich AMPs, and it has been suggested that OaBac5mini and OaBac7.5mini may use similar uptake mechanisms 34,104,112,113 .…”
Section: Amps From Mammalsmentioning
confidence: 99%
“…The use of Sbma and MdtM, which is also an inner membrane transporter 111 , facilitates the antibacterial action other proline-rich AMPs, and it has been suggested that OaBac5mini and OaBac7.5mini may use similar uptake mechanisms 34,104,112,113 . Interestingly, Sbma is of unknown physiological function 110 , but MdtM is known to be an efflux pump that contributes to the intrinsic resistance of E. coli to drugs and antimicrobials by extruding these compounds from the cytoplasm 111,114 . This co-option of transporters involved in microbial defence mechanisms to facilitate the activity of AMPs against the host microbes has been reported in a number of other cases 34,35,104 and would seem to represent an adaptation strategy in the ongoing coevolution of microbial pathogens and their hosts 115 .…”
Section: Amps From Mammalsmentioning
confidence: 99%